The Influence of Perceived Human Resource Risk Factors on Financial Problems Faced by Overberg District Municipalities - Bruwer, Juan Pierre; Rossouw, Jean-Pierre (Journal of Economics and Behavioral Studies, 2019)
Abstract: Municipalities are at the forefront of South Africa’s developmental agenda. To assist in the foregoing, the municipalities perform the primary task of service delivery - mandated by the Constitution of South Africa. The efficiency of the municipal service delivery function is depended on municipal funds, as derived from various sources. Apart from these funds, municipalities also receive funding through National and Provincial grant allocations, in addition. Notwithstanding the aforementioned most South African municipalities are experiencing financial problems which may adversely affect their relevant service delivery tasks. A possible contributor to the financial problems of South African municipalities is that of human resources (HR) risk factors. For this study, the emphasis was placed on testing whether perceived HR risk factors had any influence on the financial problems experienced in Overberg District Municipalities. Empirical research was conducted through the means of collecting quantitative primary data from 106 respondents, all of whom had to adhere to relevant delineation criteria. Stemming from the results, it was found that perceived HR risk factors did not have any statistically significant influence on the financial problems experienced in Overberg District Municipalities.